OPTIMIZATION OF PUBLIC STREET LIGHTING AT 5 POINTS FOR NIGHT MOBILITY IN SIJANGEK, SUNGAI DURIAN - Meilani, Viviana; Zahara, Leni; Zawa, Salsabila; Vernandi, Veno Maesa; Sabila, Lailam Mardiatun Ahda; Efifanny, Dea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Public Street Lighting (PJU) is a basic infrastructure that plays a strategic role in supporting community mobility, particularly at night. This study aims to describe: 1) the conditions of street lighting in Korong Sijangek before and after the reactivation of 5 street light points; 2) changes in residents' night mobility as a direct impact of optimization; and 3) community perceptions regarding the program's benefits. This research used a qualitative descriptive method, with data collected through in-depth interviews using 30 relevant questions, field observations during the Community Service (KKN) period of January–June 2026 in Korong Sijangek, Nagari Sungai Durian, Patamuan District, Padang Pariaman Regency, West Sumatra, and documentation as supporting evidence. Data were analyzed through narrative analysis covering the stages of data collection, data reduction, descriptive presentation, and conclusion drawing. Results showed that prior to reactivation, road conditions had been dark for approximately 6 months, severely limiting residents' nighttime activities and causing fear and anxiety, particularly among the elderly. After reactivating the 5 street light points, significant changes occurred, including increased safety and comfort, improved night mobility that supported social interaction, and positive impacts on micro-economic activities in local stalls. However, residents noted that distances between poles remain too far apart, and additional lighting is needed in rice field and plantation areas far from residential zones. This study concludes that optimizing 5 street light points, though a simple intervention, produced multidimensional impacts on Sijangek community mobility and can serve as a replicable model for other rural areas facing similar challenges.